PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 3 TELUK RHU - Mastura Mastura; Otang Kurniaman; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is done because the average value of IPS learning result of grade 3 students of SDN 3 Teluk Rhu is low that is 70,40 lower than Minimum Exhaustiveness Criterion (KKM) determined by school for class III that is 75. Low result of student learning caused by less learning methods involving students in learning. Learning is still dominated by teachers through lecture methods. This study is a classroom action research (PTK) consisting of two cycles, carried out in even semester 2016/2017. Subjects of this study amounted to 25 people. Of the 25 students, 11 people have been completed and 14 people are still unfinished. This study aims to improve the learning outcomes of IPS students of Class III SD Negeri 3 Teluk Rhu by applying STAD type cooperative learning model. STAD type cooperative learning model is a learning model that is implemented in the form of heterogeneous group work. Instrument of this research consists of learning tools and data collection instruments in the form of observation sheets and test kits. The study was conducted in March-April 2017. The data were analyzed using statistical analysis used for data analysis of teacher activity and student activity and improvement of student learning outcomes. Analysis of teacher and student activity is based on the observation scores made by the observer during the learning process with STAD type cooperative model. Analysis of student learning outcomes done after the implementation of daily test cycle I and cycle II. Based on scores of observation sheets of teacher and student activity, the following improvements are seen: teacher activity in cycle I reaches 54.17%, in cycle II increases 91.67% while student activity in cycle I is only 45.83%, in cycle II increases to 83,33%. Analysis of student learning result data showed improvement among others: learning mastery in cycle I 11 people, cycle II 25 people. after the application of cooperative learning model type STAD student learning outcomes increased from the average grade of 70.40 to 78.00. this means an increase of 10.79%. This shows that the application of STAD type cooperative learning model can improve the learning result of IPS students of Class III SD Negeri 3 Teluk Rhu.Keywords: STAD type cooperative model, IPS study results